Canadian translated politics at the Economic Club of New York. (2nd January 2017) - Gagnon, Chantal; Kalantari, Esmaeil
ABSTRACT: In the course of their leadership, Canadian prime ministers often make an appearance before the Economic Club of New York (ECNY). With such an event, three cultures (i.e. American, English-Canadian and French-Canadian) are at play, along with two languages. This article inquires about the political implications of translated speeches delivered by Canadian prime ministers at the ECNY, between 1978 and 2006. Using Critical Discourse Analysis and Audience Design, this study shows that the translation shifts of some speeches were potentially based on an ideological struggle between different national discourses. The study also builds on the recent notion of 'government by translation' brought forward recently in institutional translation research. The translation shifts found in the corpus can have many effects but the study focuses on two specific ones: (1) legitimisation and characterisation of linguistic communities and (2) neutralisation of Canadian territory. The results of the ECNY corpus were validated with a larger corpus of Canadian parliamentary speeches. One of the aims of this work is to contribute to the general discussion of identity in institutional translation, showing among other things how identity and power questions relate to one another in a particular discursive practice.